The Effectiveness of Web-Based Comic Media to Train Students' Creative Thinking Skills in Learning Immune System Materials - Anes Abdatul Aziz; Wiwi Isnaeni (Universitas Negeri Semarang, 2023)
The purpose of this study is to determine the effectiveness of web-based immune system comic media that has been previously developed through a development research process. This research is a pre-experimental study with typesone group pretest-posttest design. The sample of this research was students of class XI MIPA 1, XI MIPA 5, and XI MIPA 6 in one of the high schools in Purworejo. The sampling technique that was adopted in this research was cluster random sampling, involving 107 students as the total sample. In this study the learning process of the immune system material held by using web-based immune system comic media. The research data is in the form of students' creative thinking skills, types of activities in comics and their benefits for practicing creative thinking skills, and data on the implementation of teaching and learning processes. The data collection method was carried out by giving students formative tests (comic gap questions and description questions), observation sheets, and student response questionnaires. Descriptive qualitative method was used to analyze to obtained data. The research results show that creative thinking skills (could be known from the N-gain score). Student those who achieved moderate and high N-gain categories were 83% and 14% respectively (3% of students achieved low N-gain categories). The classical completeness level is 87.8%. This shows > 75% of students have achieved KKM (with good category). Based on the results of observing the learning process using comics, the information showed that the learning process that was carried out was useful to train creative thinking skills on students and the teaching and learning process can be carried out according to the RPP. The conclusion of this research is that web-based immune system comic media is effective for training students' creative thinking skills.